THE EFFECTIVENESS OF IMPLEMENTING INTERNATIONAL ISO STANDARDS IN PUBLIC ADMINISTRATION BODIES - Makhkamov, Navruzjon Tukhtamishovich (THE INNOVATION ECONOMY, 2026)
The article analyzes the current issues of implementing ISO standards in public administration bodies, their dynamics from 2015 to 2024, their effectiveness and prospects. The article examines the advantages and difficulties of implementing ISO standards based on scientific literature, international experience and practical examples in public administration in Uzbekistan. Scientific and practical recommendations are given for implementing reforms in accordance with international standards.